سلالم الحجاجية في القصة النبوية - تجاني, أمينة (جامعة الوادي - university of Eloued, 2022)
تهدف هذه الدّراسة إلى الكشف عن حجاجية قصص الحديث النّبوي ، ودورها في إقناع المتلقي والتّأثير فيه ومن ثمّة تغييره حسب الوجهة التي أرادها النّبي صلى الله عليه وسلم ، وذلك من خلال دراسة البنية اللغويّة للقصّة النّبويّة وبالتّحديد السلالم الحجاجيّة باعتبار أنّ اللغة تحمل وظيفة حجاجيّة بصفة جوهريّة بين طيّاتها تتجلى في كلماتها وعباراتها وتراكيبها . The aim of this study is to uncover the prophetic hadith stories argumentation , and its role in persuading the receiver and influencing him thus changing it according to the direction that the prophet peace be upon him wanted . that by studying the linguistic structure specifically the arguments as the language is holding an argumentative function in essence manifest in this words , phrases and its structures .
مقال
Keywords: القصة ؛ القصة النبوية ؛ الحجاح ؛ السلم الحجاجي ؛ السلم الحجاجي في القصة النبوية